Properties of C‐doped GaN. Issue 8 (26th December 2016) - Lesnik, Andreas; Hoffmann, Marc P.; Fariza, Aqdas; Bläsing, Jürgen; Witte, Hartmut; Veit, Peter; Hörich, Florian; Berger, Christoph; Hennig, Jonas; Dadgar, Armin; Strittmatter, André
Abstract : Carbon‐doping in the concentration range from [C] = 5 × 10 17 to 1.2 × 10 19  cm −3 is employed to achieve semi‐insulating properties of GaN layers as required for electronic power devices. Using propane as a carbon precursor, an independent analysis of the carbon incorporation during growth and its impact on electrical properties of the layers was obtained as growth parameters for optimum GaN quality could be applied. We observe that C is within precision of measurements fully incorporated in GaN as compensating deep acceptor. In a series of Si + C co‐doped samples, semi‐insulating properties were obtained for [C] > [Si] and the compensation efficiency for electrons is around unity. Through the extrinsic C‐doping technique previous ambiguous results on electrical and optical properties of GaN:C layers are clarified.